From Salafi Preaching to Political Preaching: Women’s Turnout and the Evolution of Salafi Movements in Egypt - Bouras, Naïma (My University, 2017)
This article investigates women’s involvement in the Salafi milieu. We ask how women follow and participate in the politicization of Salafi trends. To answer this question, we analyze, through an inductive approach, their important contributions in spreading Salafi ideology. Then, we investigate their participation – through social networks (e.g., Facebook, Egyptian media) – in the process of Salafi politicization in the aftermath of the 2011 uprising.
Keywords: Egypt; Frauenbewegung; Medien; politicization; Revolution; Salafism; women’s empowerment; ddc:303